Exploring Mental Timelines: Perceived Duration in Illiterate and Literate Individuals - Jain, Mehak (My University, 2023)
Education has become a societal norm, with the belief that educated individuals possess a higher social standing and enhanced cognitive abilities. Numerous studies have examined the impact of education on various cognitive tasks and consistently reported differential performance between literate and illiterate individuals. However, studies contradict this notion of divergent cognitive task performance among these groups. Despite this body of research, whether education influences temporal processing in literate and illiterate individuals remains to be determined. This question holds particular importance, considering that literacy involves formal training in reading and writing, which contributes to the development of a mental timeline that runs from left to Right. On this mental timeline, the left side is associated with shorter durations, while the right side is associated with longer durations. It is reasonable to assume that literate individuals, trained to read and write from left to Right, benefit from this formal training in developing their mental timeline. Conversely, illiterate individuals lack such formal training, potentially hindering the formation of their mental timeline. Therefore, the objective of this thesis is to investigate the influence of literacy on temporal processing, specifically concerning the development of the mental timeline. To accomplish this, we conducted a temporal bisection task involving two groups: literate and illiterate individuals. In this task, participants were presented with left and right arrows displaying varied durations and were asked to judge whether the presented duration was longer or shorter. These results suggest that there are no significant differences between literate and illiterate individuals in the development of the mental timeline. This implies that literacy itself may not directly influence the formation of the mental timeline, as illiterate individuals might have developed their mental timeline through different daily activities. In conclusion, this study provides insights into the relationship between literacy, temporal processing, and the development of the mental timeline. It suggests that literacy may not be the sole determinant of mental timeline formation, as individuals who lack formal literacy training can still exhibit similar temporal processing patterns. Future research could further explore the underlying factors that contribute to the development of the mental timeline in diverse populations.
Keywords: Mental Timeline; Time perception; Timings; Temporal Senstivity